Adductor pollicis muscle fatigue in women during acute altitude exposure - Fulco, C. S.; Rock, P. B.; Muza, S. R.; Lammi, E.; Moore, L. G.; Beidleman, B. A.; Lewis, S. G.; Cymerman, A. (Medicine & Science in Sports & Exercise, 1997)
Large muscle exercise performance is impaired during acute altitude exposure but there is limited information of effects on smaller muscle groups. The authors previously observed that maximal voluntary contraction (MVC) was not impaired in men but that exhaustion during submaximal adductor pollicis (small muscle) exercise occurred more quickly at altitude than at sea level. Women (N = 15) were studied at sea level and within 24 hours of exposure to 4,300 m (13,000 feet). It was found that at acute altitude without adaptation: MVC force is maintained similarly in women and men; in contrast to men, there is no impairment in time to exhaustion in women; and the similarity of time to exhaustion in women at sea level and altitude is not hormonally related to ovarian steroid levels or menstruation. Implication: The response of small muscle dynamics of women at acute altitude is similar in some respects to men, but women are able to replicate sea level time to exhaustion performances. Men fatigue easier at altitude when performing small muscle exercises.